2016
DOI: 10.1002/pchj.138
|View full text |Cite
|
Sign up to set email alerts
|

A trend toward smaller optical angles and medial‐ocular distance in schizophrenia spectrum, but not in bipolar and major depressive disorders

Abstract: Minor physical anomalies (MPAs) are subtle signs of fetal developmental abnormalities that have been considered to be among the most replicated risk markers for schizophrenia-spectrum disorders. However, quantitative approaches are needed to measure craniofacial MPAs. The present study adopted an imaging-based quantitative approach to examine craniofacial MPAs across the spectrum of schizophrenia and affective disorders, to address their sensitivity and specificity. We sampled 31 patients with schizophrenia, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…This finding is consistent with those of most studies 3 , 4 , 21 , 40 , but failed to agree with those presented in a paper published in 2016; that study reported that patients with schizophrenia have a significantly wider palate 26 . The inclusion of the high palate and furrowed tongue in both the models shows that our results are consistent with the findings that palate and tongue anomalies represent the highest prevalence of MPAs in the mouth region of patients with schizophrenia 8 , 25 , 41 , 42 . Our results revealed that patients with schizophrenia have a greater skull height and nasal width, and smaller mouth width and palate width.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with those of most studies 3 , 4 , 21 , 40 , but failed to agree with those presented in a paper published in 2016; that study reported that patients with schizophrenia have a significantly wider palate 26 . The inclusion of the high palate and furrowed tongue in both the models shows that our results are consistent with the findings that palate and tongue anomalies represent the highest prevalence of MPAs in the mouth region of patients with schizophrenia 8 , 25 , 41 , 42 . Our results revealed that patients with schizophrenia have a greater skull height and nasal width, and smaller mouth width and palate width.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a study measuring the quantitative characteristics of the eyes showed that patients with schizophrenia tended to have smaller optical angles and inner canthal distance. These results were supported by another study measuring the eye and skull regions 8 .…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…As aforementioned, MPA were not only observed in psychotic patients. Nevertheless, the association between MPA, schizophrenia and its increased genetic burden was confirmed (Hajnal et al., 2016 ; Wang et al., 2016 ). Similar profile of MPA found in HC and SSD groups is also in line with continuum model of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of MPA were also associated with a family history of schizophrenia, obstetric complications, lower number of siblings, later position in birth order and male gender (O'Callaghan et al., 1991 ). Anomalies in the craniofacial regions were also more common in patients’ unaffected relatives than in controls (Hajnal et al., 2016 ; Wang et al., 2016 ). Early onset schizophrenia (EOS) was associated with more MPA in different subsamples than in adult‐onset schizophrenia (AOS) (Green et al., 1987 ; Hata et al., 2003 ) and was in this sample linked with brain morphology abnormalities (Hata et al., 2003 ); in keeping with the notion suggesting a greater biological burden in EAO compared to AOS.…”
Section: Introductionmentioning
confidence: 99%